REVITALISASI KEARIFAN LOKAL DALAM MENJAGA LAHAN PERTANIAN PANGAN BERKELANJUTAN - Moh. Arief Rakhman; Michael Lega (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2023)
Local wisdom can be a source of strength for a more effective village development, such as a source of village regulation policies. The purposees of study are to find out how the local wisdom possessed by the people of Pasar Terusan Village is in cultivating rice and to analyze the impact of revitalizing local wisdom becoming the Village Regulation on the protection of food agricultural land. The research was conducted using qualitative methods with a descriptive approach. The collection of various data was carried out through a combination of in-depth interview, documentation and observation techniques. The form of local wisdom possessed by the people of Pasar Terusan Village can be seen from the ritual activities carried out in the process of farming and also the philosophy of livelihood that comes from rice, livestock and rubber. The revitalization of local wisdom adopted into a village regulation has successfully maintained sustainable food agricultural land, even the number of existing agricultural land increases compared to that before. In addition to customary sanctions, the welfare of community coming from the philosophy of life has its own impact on the community's choice to maintain their agricultural land.